Enhancing Firm Value in Sharia Stocks: The Interplay of Environmental, Financial Performance, and Board Gender Diversity - Ajeng Lestari; Nilawati Nilawati; Rika Lidiyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the current era, companies are required to prioritize and pay attention to employees, consumers, society and the natural environment. Investors can use firm value as a basis for seeing the company's performance in the coming period. This study aims to examine the effect of environmental performance and financial performance on firm value, with board gender diversity as a moderating variable. This study uses quantitative methods with secondary data. The sample used is 13 companies listed on ISSI and PROPER for the period 2019 - 2023. Data analysis using panel data regression with Eviews12 software. The research findings show that environmental performance has a negative effect on firm value, financial performance (EPS) has a positive effect on firm value and financial performance (ROA and DER) has no effect on firm value. Board gender diversity can strengthen the influence of environmental performance and financial performance (EPS) on firm value and board gender diversity cannot strengthen the influence of environmental performance and financial performance (ROA and DER) on firm value. Based on the results of this study, it is expected to provide the development of the concept of sustainable investment, which considers the social and environmental impacts of its investment on companies in Indonesia